2009
DOI: 10.1037/a0014713
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging the perceptual underdog: Positive affective priming of nonpreferred local–global processes.

Abstract: Two experiments examined affective priming of global and local perception.Participants attempted to detect a target which might be present as either a global or a local shape. Verbal primes were used in one experiment, and pictorial primes in the other. In both experiments, positive primes led to improved performance on the nonpreferred dimension. For participants exhibiting global precedence, detection of local targets was significantly improved, whereas for participants exhibiting local precedence, detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 80 publications
0
17
1
Order By: Relevance
“…The Eriksen Flanker task constitutes a further paradigm after the local-global task where the modulatory effects on processing affectively neutral stimuli can be reduced from a broadening (Gasper & Clore, 2002 ) to a flexibility account (Baumann & Kuhl, 2005 ; Huntsinger et al, 2010 ; Tan et al, 2009 ). In a large number of other tasks, higher flexibility due to positive affect has been observed (e.g., semantic remote-associates task: Bolte, Goschke, & Kuhl, 2003 ; Rowe et al, 2007 ; creative problem solving: Isen, Daubtman, & Nowicki, 1987 ; control processes: Dreisbach & Goschke, 2004 ; Dreisbach, 2006 ; De Vries, Holland, Corneille, Rondeel, &Witteman, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Eriksen Flanker task constitutes a further paradigm after the local-global task where the modulatory effects on processing affectively neutral stimuli can be reduced from a broadening (Gasper & Clore, 2002 ) to a flexibility account (Baumann & Kuhl, 2005 ; Huntsinger et al, 2010 ; Tan et al, 2009 ). In a large number of other tasks, higher flexibility due to positive affect has been observed (e.g., semantic remote-associates task: Bolte, Goschke, & Kuhl, 2003 ; Rowe et al, 2007 ; creative problem solving: Isen, Daubtman, & Nowicki, 1987 ; control processes: Dreisbach & Goschke, 2004 ; Dreisbach, 2006 ; De Vries, Holland, Corneille, Rondeel, &Witteman, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although no evolutionary motivation for it has been posited, the broadening hypothesis holds that positive affect extends spatial attention to large-scale stimulus features. Both flexibility (e.g., Baumann & Kuhl, 2005 ; Heerebout, Todorović, Smedinga, & Phaf, 2013 ; Tan, Jones, & Watson, 2009 ; but see Huntsinger, Clore, & Bar-Anan, 2010 ) and broadening hypotheses (Gasper & Clore, 2002 ; Rowe, Hirsh, & Anderson, 2007 ) have received ample empirical support. This study aims to show that one of the findings supporting the spatial hypothesis is more consistent with the temporal hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…One suggestion is an impairment in global vs. local visual processing. “Global processing” refers to the ability to attend to any visual stimulus as a “whole,” as opposed to its component features (Tan et al, 2009). Studies of schizophrenia have revealed impairments in global processing, but largely preserved local processing both for static (Goodarzi et al, 2000; Silverstein et al, 2000; Johnson et al, 2005; Poirel et al, 2010) and dynamic stimuli (Chen et al, 2003).…”
Section: Does Impaired Identity Processing Reflect a Generalized Attementioning
confidence: 99%
“…This increased behavioral flexibility, moreover, is supported by ample empirical research in which positive affect was found to increase cognitive and behavioral flexibility (Baumann & Kuhl, 2005;Das & Fennis, 2008;Dreisbach & Goschke, 2004;Fenske & Eastwood, 2003;Isen, 1999;Luu, Tucker, & Derryberry, 1998;Tan, Jones, & Watson, 2009). The broaden-and-build theory of Fredrickson (1998), for instance, generalizes these ideas even further by assuming that positive emotions serve to broaden an individual's momentary thought-action repertoire by expanding the attentional focus.…”
Section: New Simulations Reveal Stimulus-specific Frequencymentioning
confidence: 70%
“…The comparison can even be taken one step further, because affective influences also have been found on the attentional blink (Olivers & Nieuwenhuis, 2006; see also Most, Chun, Johnson, & Kiehl, 2006;Todorović, 2009, recently obtained similar affective modulation of the attentional blink in our laboratory). There is substantial evidence for the hypothesized link between affect and attentional switching not only for the attentional blink task, but also for other experimental tasks (Baumann & Kuhl, 2005;Das & Fennis, 2008;Dreisbach & Goschke, 2004;Fenske & Eastwood, 2003;Isen, 1999;Luu et al, 1998, Tan et al, 2009. In comparison, the empirical evidence for a relationship between affect and oscillation frequency is much scarcer.…”
Section: New Simulations Reveal Stimulus-specific Frequencymentioning
confidence: 96%